2017
DOI: 10.1016/j.bbadis.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of α-smooth muscle actin in fibroblast-mediated matrix contraction and remodeling

Abstract: Cardiac myofibroblasts play an important role in myocardial remodeling. Although α-smooth muscle actin (α-SMA) expression is the hallmark of mature myofibroblasts, its role in regulating fibroblast function remains poorly understood. We explore the effects of the matrix environment in modulating cardiac fibroblast phenotype, and we investigate the role of α-SMA in fibroblast function using loss- and gain-of-function approaches. In murine myocardial infarction, infiltration of the infarct border zone with abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
257
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(298 citation statements)
references
References 54 publications
15
257
0
1
Order By: Relevance
“…As the neutrophil infiltrate is cleared by macrophages, fibroblasts expand and undergo myofibroblast transdifferentiation [13], expressing contractile proteins, such as α-smooth muscle actin (αSMA) (Figure 1), and secreting large amounts of extracellular matrix proteins [27],[28]. Activated fibroblasts play a critical role in preservation of the structural integrity of the infarcted ventricle [10]; however excessive or prolonged activation of fibroblast populations may reduce ventricular compliance, promote adverse remodeling and precipitate heart failure [29].…”
Section: The Fibroblasts During the Proliferative Phase: Myofibroblasmentioning
confidence: 99%
“…As the neutrophil infiltrate is cleared by macrophages, fibroblasts expand and undergo myofibroblast transdifferentiation [13], expressing contractile proteins, such as α-smooth muscle actin (αSMA) (Figure 1), and secreting large amounts of extracellular matrix proteins [27],[28]. Activated fibroblasts play a critical role in preservation of the structural integrity of the infarcted ventricle [10]; however excessive or prolonged activation of fibroblast populations may reduce ventricular compliance, promote adverse remodeling and precipitate heart failure [29].…”
Section: The Fibroblasts During the Proliferative Phase: Myofibroblasmentioning
confidence: 99%
“…α-SMA is a major differentiation marker of myofibroblasts, which are more contractible and synthesize higher amounts of extracellular matrix proteins. 23 α-SMA-containing stress fibres have an arrhythmic effect on cardiomyocytes. 24 These effects may contribute to the increasing risk of AF in patients with Pitx2c deficiency with its known electrophysiological effects in the atrium and enhanced genesis of pulmonary vein myocardial sleeves.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, for the first time, we found that Pitx2c deficiency increased atrial fibroblast activity with increasing migration and higher expression of α‐SMA. α‐SMA is a major differentiation marker of myofibroblasts, which are more contractible and synthesize higher amounts of extracellular matrix proteins . α‐SMA‐containing stress fibres have an arrhythmic effect on cardiomyocytes .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that either a longer time in co‐culture with EC or additional factors from, for example, keratinocytes are required for ASC to fully differentiate into myofibroblasts. It has also been shown that MSC are able to contract tissue in an α‐SMA independent manner, via microfilaments (Dawes et al, ; Shinde, Humeres, & Frangogiannis, ).…”
Section: Discussionmentioning
confidence: 99%